Ocean thermal energy conversion (OTEC) system boosted with solar energy and TEG based on exergy and exergo-environment analysis and multi-objective optimization. (15th September 2020) - Malik, Muhammad Zeeshan; Musharavati, Farayi; Khanmohammadi, Shoaib; Baseri, Mohammad M.; Ahmadi, P.; Nguyen, Dinh Duc
Graphical abstract: Highlights: To propose a solar based OTEC system for electricity and H2 production. To utilize the rejected heat to produce electricity using TEG. To see the effect of employing TEG on the H2 production rate. To determine Pareto surface of proposed energy system. Abstract: The primary goal of the current study is thermodynamic and environmental modeling and multi-objective optimization of a new hybrid energy system. The suggested ocean-based energy conversion system consists of an organic Rankine cycle (ORC), a solar flat plate collector, a proton exchange membrane (PEM) electrolyzer boosted with thermoelectric generator (TEG) module. Exergy and exergo-environmental as two powerful tools are employed to the precise assessment of the suggested system. To achieve the best performance of the integrated system, multi-criteria optimization with different objective functions is carried out. As the results of the parametric analysis indicate, defined objective goals have an appropriate conflict with changing decision variables, which is necessary in multi-criteria optimization. Four decision variables namely solar flat plate collector area ( A p ), solar radiation intensity ( I ), collector temperature ( T col ), and condenser temperature ( T cond ) are chosen as decision variables. In all optimization scenarios, the net output power is common, which is based on the selected optimum points value changing between 201.02 kW and 268.17 kW. Additionally, in various optimization scenarios, the area of solar flat plate collectors tends to get a higher value in the allowable domain. The provided information in multi-objective optimization can provide good insight to engineers and system designers to select the best system configuration.